Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5604/17322693.974647
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns as risk factors of differentiated thyroid carcinoma

Abstract: Dietary patterns appear to modify the risk of thyroid carcinoma. A diet rich in vegetables and fruit, as well as saltwater fish (a source of iodine) and low-fat meat, could be an important protective factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Very little information is available on the relationship between TC risk and the intake of energy and main energy sources. Case-control studies from Brazil,10 Italy,25 and Poland26 showed that higher intake of energy, and rich-carbohydrate sources among TC cases as compared to controls. In a case-control study from French Polynesia, bread, rice and pasta were included in a “Western dietary pattern” that was also positively associated with elevated risk of differentiated TC 15.…”
Section: Discussionmentioning
confidence: 98%
“…Very little information is available on the relationship between TC risk and the intake of energy and main energy sources. Case-control studies from Brazil,10 Italy,25 and Poland26 showed that higher intake of energy, and rich-carbohydrate sources among TC cases as compared to controls. In a case-control study from French Polynesia, bread, rice and pasta were included in a “Western dietary pattern” that was also positively associated with elevated risk of differentiated TC 15.…”
Section: Discussionmentioning
confidence: 98%
“…The process is depicted in the flowchart (Figure ). Fourteen studies were excluded for the following reasons: (1) for presenting the total number of only thyroid cancers in general and not by their subtypes; (2) presenting odds ratios (ORs) without the total number of subjects involved; (3) analyzing food items with minimal iodine contents; and (4) being unclear in the distinction between periods before and after salt iodization . After the exclusion steps, we included 16 studies for the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a case-control study including 284 thyroid cancer cases showed that thyroid cancer patients drank less coffee than healthy patients [12]. However, a pooled analysis of 14 case-control studies from 1980 to 1997 including 2725 thyroid cancer cases reported that there were no clear trends in thyroid cancer risk by level of coffee consumption (a summary odds ratio, OR = 0.9, 95% confidence interval, CI = 0.8–1.1) [13].…”
Section: Introductionmentioning
confidence: 99%